Development of Multimedia-Based Interactive Module Teaching Materials to Increase Learning Independence Learners - Septi Suarmita; Suarman Suarman; Gusnardi Gusnardi (Global READ Center, 2025)
This research aims to develop multimedia-based interactive module teaching materials. This research uses the method Research and Development (R&D), a 4D model developed by Thiagarajan, Semmel, and Semmel which includes the definition stage, design stage, development stage and deployment stage. Data was collected from the assessments of 5 experts through expert validation sheets and responses from 38 students through student response questionnaires. Data analysis uses quantitative descriptive techniques. The results of the research show that the interactive module teaching materials are suitable for learning in Basic Accounting subjects from material experts with valid categories and the results of product trials, it is known that the interactive module teaching materials are effective in increasing students' learning independence, especially in the basic accounting equation material in vocational school. The students' positive response to the use of this interactive module teaching material, the majority of students stated that it was useful and at the same time could increase their learning independence, especially in the basic accounting equations material.